2021
DOI: 10.1016/j.tranon.2021.101043
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cholesterol on cancer progression and therapy

Abstract: Highlights Abnormality in blood cholesterol level is significantly correlated with risk of different cancers. Majority of tumor tissue from cancer patient exhibits overexpression of LDLR and ACAT for supporting rapid cancer cell proliferation. Alteration of the cholesterol metabolism in cancer cells hampers therapeutic response. Targeting cholesterol metabolism for treatment of cancer with other conventional chemotherapeutic drugs appear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(64 citation statements)
references
References 217 publications
2
50
0
Order By: Relevance
“…It was reported that cholesterol accumulation was associated with chemoresistance [ 21 ]. On the other hand, we noticed that Squalene acts as the substrate of Squalene Epoxidase (SQLE) for cholesterol biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that cholesterol accumulation was associated with chemoresistance [ 21 ]. On the other hand, we noticed that Squalene acts as the substrate of Squalene Epoxidase (SQLE) for cholesterol biosynthesis.…”
Section: Resultsmentioning
confidence: 99%
“…To maintain continuous proliferation cancer cells may reprogram cholesterol metabolisms, including interaction to extracellular environment through the influx and efflux, de novo synthesis, and multiple intracellular regulatory pathways, among which, reversible conversion of free cholesterol and CE could be the most fast and cost/effective way to obtain free cholesterols. Previously, studies on changes in cholesterol metabolisms in CRC mostly focused on diet intake, systemic level, uptake by cancer cells, and de novo synthesis of free cholesterol [ 19 ]. However, there were scarcely reports on the process of intracellular conversion between free cholesterol and CE.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that in colorectal cancerous tissue, the levels of cholesterol and triglycerides were reduced and HDL-Cholesterol level increased, indicating that CRC development destroys the physiological balance of lipids and lipoproteins, leading to lipid metabolic disorders [40]. Preclinical and clinical studies have already investigated the role of cholesterol in CRC progression; however, a clear understanding of the molecular mechanism linking these two entities is still lacking [40,41].…”
Section: Discussionmentioning
confidence: 99%